Zakat Sanitasi Dalam Pandangan Islam - Halili Halili (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2020)
Zakat is the third pillar of Islam that must be performed by Muslims worldwide. It is an obligation that all Muslims fulfill by giving basic foods and other wealth. In return, some of the underprivileged and deserving groups enjoy donations from fellow Muslims. Zakat is not receiving certain assets prescribed by religion. Rather, Zakat is donated in the form of benefits that may be categorized as things that are quite needed. Such as the donation of clean water after reviewing the amount of water that is not suitable for consumption and use. Another example is the benefit of sanitation that has efforts to reduce the symptoms of infectious and dangerous diseases. The formulation of the problem in this study is how the form of sanitation zakat and how the view of Islamic law on sanitation zakat. The data analysis method used in this research is descriptive qualitative method. In this study there are two things that will be analyzed, namely sanitation zakat and sanitation zakat in the view of Islam. Observation or observation is a data collection activity used to collect data in research through the five senses or can be interpreted as observation in systematic recording of symptoms that appear on the object of research. Sanitation in principle is a deliberate behavior in the culture of clean living with the intention of preventing humans from direct contact with dirt and other hazardous waste materials, with the hope that this effort will maintain and improve human health. Waste materials can cause health problems. These include human or animal feces, solid waste materials, domestic waste water (laundry, urine, bathing or laundry waste materials), industrial waste materials and agricultural waste materials.